2014
DOI: 10.1063/1.4882436
|View full text |Cite
|
Sign up to set email alerts
|

Spot size dependence of laser accelerated protons in thin multi-ion foils

Abstract: We present a numerical study of the effect of the laser spot size of a circularly polarized laser beam on the energy of quasi-monoenergetic protons in laser proton acceleration using a thin carbon-hydrogen foil. The used proton acceleration scheme is a combination of laser radiation pressure and shielded Coulomb repulsion due to the carbon ions. We observe that the spot size plays a crucial role in determining the net charge of the electron-shielded carbon ion foil and consequently the efficiency of proton acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In order to successfully accelerate the protons by the Coulomb repulsion force, we should both reduce the charge difference between carbon ions and electrons and keep the electrons from returning to the carbon layer so that the net charge of the carbon-electron layer is positive. In our previous works [32,33], we concluded that a higher carbon concentration and smaller spot size can lead to increased proton energy.…”
Section: Introductionmentioning
confidence: 78%
“…In order to successfully accelerate the protons by the Coulomb repulsion force, we should both reduce the charge difference between carbon ions and electrons and keep the electrons from returning to the carbon layer so that the net charge of the carbon-electron layer is positive. In our previous works [32,33], we concluded that a higher carbon concentration and smaller spot size can lead to increased proton energy.…”
Section: Introductionmentioning
confidence: 78%
“…As a result, it also affects the properties of the beams of particles and radiation generated by those electrons. In the case of beams of ions accelerated by the target normal sheath acceleration (TNSA) mechanism 7 , it has been demonstrated to change the energy spectrum, spatial distribution and laser-to-ion energy conversion efficiency 18 23 .…”
Section: Introductionmentioning
confidence: 99%